2008
DOI: 10.1080/09595230701829371
|View full text |Cite
|
Sign up to set email alerts
|

Can music therapy engage patients in group cognitive behaviour therapy for substance abuse treatment?

Abstract: Music therapy is a promising approach to improving engagement in substance abuse treatment groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(50 citation statements)
references
References 35 publications
3
41
0
1
Order By: Relevance
“…Participation was employed as a proxy for engagement in two studies (Dingle et al, 2008; but in an earlier study the reverse was the case; i.e. engagement was employed as a proxy for participation (Nelson & Borkovec, 1989).…”
Section: Engagement As Participation or Involvementmentioning
confidence: 99%
See 1 more Smart Citation
“…Participation was employed as a proxy for engagement in two studies (Dingle et al, 2008; but in an earlier study the reverse was the case; i.e. engagement was employed as a proxy for participation (Nelson & Borkovec, 1989).…”
Section: Engagement As Participation or Involvementmentioning
confidence: 99%
“…Motivation (Dingle et al, 2008), intentions (Klag et al, 2010) or commitment (Joe et al 1999) to participate, rather than the acts of participation, have been employed as proxies for engagement. Motivation can predict behavior (Chatzisarantis, Hagger, Smith, & Sage, 2006) and has thus been conceptualized by some researchers (e.g.…”
Section: Engagement As Participation or Involvementmentioning
confidence: 99%
“…As shown by Gold et al, music therapy has strong and significant effects on global state, level of general symptoms, negative symptoms, depression, anxiety, and functioning. It has also been shown recently that music therapy can improve engagement in a cognitive behavior therapy group (Dingle, Gleadhill, & Baker, 2008).…”
Section: Dialectical Behavior Therapy For Adolescentsmentioning
confidence: 98%
“…Bensimon, Amir, and Wolf (2007) reported that individuals with PTSD who engaged in drumming reported several positive outcomes, including being more open, having greater self-control, feeling a sense of belonging, feeling closer to others, accessing memories and expressing emotions productively. Music has also been used with individuals with mood disorders (Maratos, Gold, Wang, & Crawford, 2009) and with individuals with substance abuse disorders (Dingle, Gleadhill, & Baker, 2008).…”
Section: A Formal Practice Emergesmentioning
confidence: 99%